Simultaneous time imaging, velocity estimation and multiple suppression using local event slopes - Cooke, D.; Bona, Andrej; Hansen, B. (Society of Exploration Geophysics, 2008)
We present and discuss the use of local event slopes and their associated attributes (referred to as XTP attributes here) as a way to estimate a time-imaging velocity field and to suppress organized noise including – but not restricted to - multiples. The 4 XTP attributes are: migration velocity, migrated spatial location, migrated zero offset time and stack domain dip. We derive the equations for XTP attributes from the double square root equation which illustrates the strong connection with Kirchhoff time migration. In this paper the XTP attributes are calculated in the shot and receiver domain. The advantages of shot/ receiver domain XTP noise suppression over similar efforts in the CMP and offset domain are discussed. In a companion presentation (Cooke et al, 2008), we discuss different methods of extracting these local event slopes.